1997
DOI: 10.1090/s0002-9947-97-01804-7
|View full text |Cite
|
Sign up to set email alerts
|

Enriched 𝑃-Partitions

Abstract: Abstract. An (ordinary) P -partition is an order-preserving map from a partially ordered set to a chain, with special rules specifying where equal values may occur. Examples include number-theoretic partitions (ordered and unordered, strict or unrestricted), plane partitions, and the semistandard tableaux associated with Schur's S-functions. In this paper, we introduce and develop a theory of enriched P -partitions; like ordinary P -partitions, these are order-preserving maps from posets to chains, but with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
249
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(254 citation statements)
references
References 16 publications
3
249
0
2
Order By: Relevance
“…Second, combinatorics of peaks of permutations has been recently reviewed by J. Stembridge in Ref. [19]. The peak algebra of Stembridge is a certain sub-algebra of the algebra of polynomials with infinitely many variables.…”
Section: Resultsmentioning
confidence: 99%
“…Second, combinatorics of peaks of permutations has been recently reviewed by J. Stembridge in Ref. [19]. The peak algebra of Stembridge is a certain sub-algebra of the algebra of polynomials with infinitely many variables.…”
Section: Resultsmentioning
confidence: 99%
“…Remark 4.13. In [20], the author also gave the following refinement of Schur's Q-functions in terms of peak functions:…”
Section: Quasisymmetric Schur P-functionsmentioning
confidence: 99%
“…, a k } we have M S β€² = M (a1+1,...,a k βˆ’a kβˆ’1 , nβˆ’a k ) . Stembridge [28] showed that the Abelian group Ξ  βŠ‚ Qsym generated by the functions ΞΈ S is a subring, and rk Ξ  2n = c nβˆ’1 . According to [55], the ring Ξ  is a Hopf subalgebra.…”
Section: Appendix C the Stembridge Algebramentioning
confidence: 99%
“…The algebra Ξ  was introduced in [28] for studying so-called enriched P -partitions. One can show (see [56], and see Appendix E) that the algebra L * (D * ) βŠ— Q = R * (D * ) βŠ— Q βŠ‚ Qsym βŠ— Q defined by the conditions of Corollary 7.7 coincides with the Stembridge algebra Ξ  βŠ— Q.…”
Section: Appendix C the Stembridge Algebramentioning
confidence: 99%
See 1 more Smart Citation